Investigating the physiotherapy management of patients with polytrauma admitted to acute care settings and factors that influence service delivery after discharge: a Namibian survey - Chirombo, Hannah E. (University of the Witwatersrand, Johannesburg, 2024)
Introduction: Globally 5.8 million deaths per year are because of multiple traumatic injuries with as much as 16,000 deaths a day. Traumatic physical injuries thus pose a notable risk worldwide resulting in morbidity and mortality. Most commonly road traffic collisions are the largest contributing factor to traumatic physical injuries. Namibia ranks highly in Africa in the proportion of cases of motor vehicle crashes (MVC) per population and are the fifth leading cause of death. With Namibia also ranking highly on violence, many people often require rehabilitation following physical trauma. Delivery and accessibility of rehabilitation services in Namibia is hindered by a critical shortage of rehabilitation service providers employed by the state as most are attracted by the private sector. In the existing literature, auditing of usual care physiotherapy practice following polytrauma is not frequently documented. For a country with a high incidence of MVCs, it is imperative to look at usual care in physiotherapy for patients with polytrauma. Aim: To describe the physiotherapy management of patients with polytrauma in acute care settings in Namibia and the factors that influence service delivery to these patients after discharge. Methodology: A cross-sectional survey was conducted using an electronic survey tool. A study-specific questionnaire was developed, and content validation of the questionnaire was conducted by two physiotherapy experts in the field of traumatology. Convenience sampling was used to invite all registered physiotherapists practicing in Namibia’s state and/or private acute care facilities to participate (n=133). Descriptive statistics were used to summarise the data. Categorical data was summarized as frequencies and percentages and presented in tables, pie charts, and graphs. Continuous data were summarised as medians and interquartile ranges. Qualitative content analysis was done on data obtained from patients’ answers to open-ended questions. Results: Fifty-five questionnaire links were opened by the respondents; 52 responses were considered in this study yielding a 39% response rate (n=52/133). Female physiotherapists made up most of the respondents (n= 33; 64%). Most respondents were young with a median age of 30 years (IQR= 28-31) and an average of six years (IQR= 3.3-7) of clinical practice. Respondents worked in private institutions (n=18; 35%), public sector (n=16; 31%) and both public and private sector (n=18; 35%). The majority of the respondents encountered patients with polytrauma in the ICU setting and hospital ward. Most participants (n=47, 93%) reported that majority of the patients with polytrauma that they see in their places of work are males. The most frequent mechanism of injury resulting in polytrauma was motor vehicle crashes (n= 47; 93%), whilst stab wounds and gunshot wounds were rare causes of polytrauma. Frequently injured body regions were the lower limb (n=40; 77%) and head and neck (n=37; 71%). Physiotherapists commonly used breathing exercises (n=44; 85%), suctioning (n=42; 81%), manual chest therapy (n=39; 75%), body positioning to optimize oxygenation (n=38; 73%), respiratory muscle strengthening (n=35; 67%), active cycle of breathing techniques (n=34; 65%), incentive spirometry (n=34; 65%), positive expiratory pressure therapy (n=31; 60%), body positioning to aid postural drainage (n=28; 54%) and nebulisation therapy (n=25; 48%) to optimize/restore their polytrauma patients’ respiratory function. Whilst manual hyperinflation (n=32; 62%), ventilator hyperinflation (n=29; 56%) and intermittent positive pressure breathing (n=27; 52%), were ‘rarely used’. Physiotherapists frequently used early mobilisation out of bed (n=49; 94%), active range of motion (n=48; 92%), passive ROM (n=48; 92%), in bed mobilisation (n=46; 89%), and functional exercises (n=42; 81%) to restore/maintain optimal neuromusculoskeletal system function in patients with polytrauma. These techniques were immensely popular among respondents such that no one reported not using them in patient care. In the evaluation of treatment of the neuromuscular system the de Morton mobility index (n= 41; 78%), physical function in intensive care unit test (n=35; 67%) and Chelsea critical care physical assessment tool (n=34; 67%) were validated outcome measures ‘rarely used’ by most of the respondents, whilst the evaluation of muscle power (n=43; 83%), and medical research council sum score (n=43; 83%) were frequently used. Patients with polytrauma stayed between eight to 15 days and were then discharged into step-down facilities (n= 25; 48%), and subacute facilities of the same institution (n= 19; 37%) for extended care whilst some were discharged home (n= 21; 40%). Functional outcomes and hospital length of stay were factors reported to influence patients’ discharge. Respondents reported that they routinely provided home exercise programs focused on respiratory rehabilitation, cardiopulmonary endurance training, and patient and caregiver education to their patients. The lack of adequate human resources in the physiotherapy profession and insufficient knowledge by team members in Namibia about the role of physiotherapy in the care of patients with polytrauma injury were factors reported to affect in-hospital physiotherapy service delivery. Inadequate support systems for patients by their family/caregivers and the long distances that patients need to travel to access rehabilitation services after hospital discharge were factors reported to affect the continuity of physiotherapy service provision after discharge from an acute care facility. Good family support (n=11; 21%) as well as patient’s self-motivation and compliance to their treatment (n=10; 19%) were factors reported as enablers to physiotherapy service provision post-discharge. Conclusion: In Namibian acute care settings, patients with polytrauma are mostly male, sustained injury through motor vehicle crashes, and had an extended hospital stay before discharge to step-down facilities. Physiotherapy management is focused on prevention of respiratory system dysfunction and all physiotherapists prioritized active exercises and mobilisation out of bed in their patient management. Findings contribute to the limited existing body of knowledge regarding the physiotherapy management of Namibian patients who sustained polytrauma injury. The limited use of physiotherapy techniques that require adjustment of mechanical ventilator settings and the limited use of validated outcome measures by physiotherapists in their patient management are highlighted. The lack of human and financial resources are factors reported to impact physiotherapy service delivery in Namibia. Implications for clinical practice: Findings from this study provide a platform from which intervention- based studies can be conducted to better understand the effect of physiotherapy management on patient outcomes after polytrauma
A research report submitted in partial fulfillment of the requirements for the degree of Masters of Science in Physiotherapy to the Faculty of Health Sciences, School of Physiotherapy, University of the Witwatersrand, Johannesburg 2024
Keywords: Polytrauma; Acute Care; Mobilisation; Exercise; Service Delivery; UCTD; SDG-3: Good health and well-being